Peranan Room Attendant dalam Menjaga Kebersihan Kamar Tamu di U Paasha Seminyak Bali - Arini, Ni Nyoman; reynaldi, ade; Sunarprasetyo, mahardjono; Anggreni, Ni Putu Yunik (HARMONY HOSPITALITY, 2022)
This research has a background problem including, the fluctuating cost of room occupancy rate every month. Therefore, the author raised the title of the study about the role of room attendant in maintaining the cleanliness of guest rooms at Hotel U Paasha Seminyak Bali. The method used is descriptive qualitative as for the research objectives to determine the role of the room attendant in maintaining the cleanliness of the guest rooms, to find out the obstacles faced by the room attendant in maintaining the cleanliness of the guest rooms, to find out the efforts made by the room attendant in maintaining the cleanliness of the guest rooms at the U Paasha hotel. Seminyak Bali. The results of this study are room attendants are able to complete work during high season by looking for daily workers and carrying out inventory every month to find out supplies of tools and materials and if there is a shortage of linen the room attendant will report to the supervisor that there is a shortage of linen and the supervisor immediately reports to the executive housekeeper. Obtained from primary data and secondary data. Using research instruments to improve research results. Data collection techniques by means of observation, interviews and documentation. Also using data analysis techniques. The technique of presenting the results of the analysis where the presentation of the results of this analysis aims to fully clarify what can be obtained at the hotel.